Chapter "Куда бы тебя ни занесло...". Connettivi concessivi o fraseologismi sintattici? - Cotta Ramusino, Paola (Biblioteca di Studi Slavistici, 2018)
This paper analyses the concessive connectives - like, for example, "Куда бы тебя ни занесло/где бы она ни была..." - introducing universal concessive conditional clauses from the point of view of Construction Grammar. The analysis aims to account for the lexical, morphosyntactic and semantic-pragmatic conditions to be realized in order to show the phrasematic nature of this group of conjunctions. In doing so we address also the role of the expletive negation in this construction, which is of crosslinguistic relevance.